The Extent of the Effect of Administrative Contracts to Third Parties - Batarseh, Sulaiman; Aljazi, Jehad Dhifallah; Hasan, Suhair (Dirasat: Shari’a and Law Sciences, 2020)
Management activity is based on two important methods, one of which is unilateral, represented by administrative decisions, and the other is contractual, represented by administrative contracts. Administrative contracts are distinguished from contracts concluded by individuals among themselves to organize and manage public utilities and achieve public benefits. Whatever the legal basis provided by administrative jurisprudence to justify the extension of the effects of the administrative contract to third parties, whether the theory of conditionality for the benefit of third parties or the theory of the subjective nature of administrative contracts or others, it is agreed that the burdens and obligations borne by third parties from administrative contracts are only a natural consequence of the privileges enjoyed by the contractor with the administration. The research was divided into three topics: the first dealt with the legal basis for the extension of the administrative contract to third parties, rights derived by third parties from the administrative contract, and obligations imposed by the administrative contract to third parties. The researchers reached to several conclusions: the laws and legislations regulating the subject of administrative contracts do not address the inclusion of texts that clearly and comprehensively address the issue of the relative impact of the contract, and the extent to which it applies to the administrative contract. The study recommended to expand the jurisdiction of the administrative judiciary in Jordan to include the consideration of all disputes arising from administrative contracts, and not only the determination of administrative decisions separable from these contracts